Method for preparing Fe-based bifunctional monolithic catalyst based on double chloride water corrosion method and application of Fe-based bifunctional monolithic catalyst
The preparation of Fe-based bifunctional integrated catalysts through dichloride water corrosion method and heat treatment technology has solved the problems of complex catalyst synthesis conditions and easy loss of powder catalysts, and achieved efficient and stable catalyst preparation and wastewater pollutant degradation.
Patent Information
- Application Number
- CN202510062114.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing catalyst synthesis conditions are complex, and the large-scale application is limited. The powder catalyst has problems such as easy loss and blockage. The traditional preparation method requires special equipment and harsh reaction conditions, which increases production costs and environmental pollution.
The Fe-based bifunctional integral catalyst was prepared by the dichloride water corrosion method. The iron foam and dichloride were corroded in dilute acid to form bimetal hydroxide, and then converted into bimetal oxide through heat treatment to achieve in-situ growth and stability improvement of the catalyst.
This method simplifies the preparation process of the catalyst, reduces production costs, improves the stability and activity of the catalyst, and can efficiently degrade pollutants in wastewater at room temperature and normal pressure, avoiding the shedding and secondary pollution of the active material.
Smart Images

Figure CN119869545A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and specifically relates to a method for preparing an Fe-based bifunctional integral catalyst based on a double chloride water corrosion method and an application thereof in treating organic pollutants. Background Art
[0002] At present, advanced oxidation reactions are considered to be an effective method for removing organic pollutants from wastewater. The principle is to produce a large amount of active oxidizing substances that can degrade most organic pollutants through the activation of periodate. However, homogeneous catalysts are difficult to recover due to their solubility in water and may cause secondary pollution, which limits their practical application. Therefore, heterogeneous periodate oxidation systems have gradually attracted widespread attention due to their higher catalytic efficiency, better stability and lower operating costs.
[0003] Generally speaking, catalysts used for catalytic oxidation are divided into two categories based on the existing forms, namely powdered catalysts and self-supporting catalysts. However, powdered catalysts face problems such as easy loss and clogging, while self-supporting catalysts can effectively overcome these problems. Currently, most commonly used self-supporting catalyst materials are carbon-based materials, such as carbon paper, carbon felt and carbon cloth. However, due to the steric hindrance effect between the substrate and the active substance, it is difficult for the active sites to be evenly anchored on the surface of the material, affecting the catalytic performance. In addition, common methods for preparing self-supporting double metal (oxy) hydroxides include electrochemical deposition, ion exchange and hydrothermal synthesis, etc. These traditional preparation methods require special equipment and harsh reaction conditions, increase production costs and environmental pollution, and limit the promotion of Fenton-like reactions in practical applications. Patent CN 103951016A discloses a method for treating nitrogen-containing wastewater using an iron-carbon composite agent, which is catalyzed by activated carbon and ordinary iron powder, but the catalytic efficiency is low, and the iron powder is easily oxidized and deactivated. Patent CN 106229153A discloses a method for preparing a carbon cloth loaded nickel oxide coated iron oxide nanorod composite material, using a hydrothermal method to grow iron oxide nanorods on carbon cloth, but the hydrothermal method needs to react in a closed environment under a certain pressure, and the preparation process is complicated, energy consumption is high and the cost is high. Patent CN 111313041A discloses a method for preparing a nickel iron hydroxide electrocatalyst, which is prepared by dissolving iron salt, fluorine-containing compound and urea in water, immersing nickel foam in the solution, and performing a hydrothermal reaction to obtain a nickel iron hydroxide electrocatalyst. However, the method reacts with a nickel foam substrate through an iron salt solution, and only forms nickel iron hydroxide on a nickel foam substrate with a limited surface area, resulting in a limited specific surface area and pore structure, and a low iron loading, and poor stability for long-term use. Therefore, it is urgent to develop a simple, economical and environmentally friendly synthesis method to prepare a self-supporting bimetallic (oxy) hydroxide.
[0004] Metal corrosion is a common spontaneous process in the natural environment, which usually leads to serious material failure and engineering damage, causing huge economic losses to society. In order to prevent metal corrosion, people have taken a lot of measures, such as pigment coating, electrochemical protection and addition of corrosion inhibitors. Although significant progress has been made in corrosion prevention, research on the functional utilization of corrosion phenomena is still relatively scarce. In recent years, inspired by the concept of "turning harm into benefit", the preparation of catalysts using corrosion processes has become an emerging research direction, providing an innovative perspective for the development of technologies such as catalysis. The corrosion method shows high versatility and scalability due to its low requirements for energy input, temperature, pressure and reactor configuration. As a new strategy for catalyst synthesis, the significant advantages of corrosion engineering are: simple synthesis process, strong controllability, easy large-scale production and low cost. Therefore, as a promising technology for preparing efficient catalysts using the self-corrosion reaction of metal materials, corrosion engineering has important research and development value. Summary of the invention
[0005] In order to solve the problems of complex synthesis conditions of existing catalysts, limited large-scale application, and easy loss and clogging of powdered catalysts, the present invention provides a method for preparing an Fe-based bifunctional integral catalyst based on a double chloride water corrosion method and its application, aiming to make the prepared catalytic material have a stable structure, high activity, and can efficiently degrade pollutants in wastewater at room temperature and normal pressure.
[0006] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0007] The present invention first provides a method for preparing an Fe-based bifunctional monolithic catalyst based on a double chloride water corrosion method, which is carried out according to the following steps:
[0008] Step 1, immersing the foam iron in dilute hydrochloric acid for ultrasonic cleaning to remove oxides on the surface of the foam iron, then rinsing with ultrapure water to remove residual dilute hydrochloric acid, then immersing the foam iron in anhydrous ethanol for ultrasonic cleaning to remove organic pollutants on the surface of the foam iron, rinsing with anhydrous ethanol after the ultrasonic cleaning, and finally drying in an oven to obtain material A;
[0009] Step 2: dissolving dichloride NaCl and MCl in ultrapure water, stirring evenly to obtain material B; placing material A into material B, stirring at room temperature, and obtaining material C through a spontaneous metal corrosion process;
[0010] Step 3: Wash material C with ultrapure water and anhydrous ethanol in turn, then place the washed material C in an oven to dry to obtain material D, and finally place material D in a tubular furnace and calcine under inert gas protection to obtain the target product.
[0011] More preferably, in step 1, the concentration of the dilute hydrochloric acid is 0.1 to 1 mol / L.
[0012] Further preferably, in step 2, the molar ratio of NaCl and MCl constituting the double chloride is 0.5:0.1-0.5, wherein M is Mn, Ni, Zn or Co.
[0013] More preferably, in step 2, the stirring time at room temperature is 12 to 16 hours.
[0014] More preferably, in step 3, the calcination conditions are: firstly heating to 200-500°C at a heating rate of 2-3°C / min, keeping the temperature for 1-2h, and then naturally cooling to room temperature.
[0015] More preferably, in step 3, the inert gas is at least one of argon and nitrogen.
[0016] More preferably, in step 1 and step 3, the drying is performed at 60-80° C. for 6-10 hours.
[0017] The present invention further provides an application of the Fe-based bifunctional integral catalyst prepared according to the above preparation method in the treatment of organic wastewater, which can be specifically as follows: in the presence of the Fe-based bifunctional integral catalytic material, wastewater containing organic pollutants contacts and reacts with an oxidant to obtain purified water after the reaction.
[0018] Further preferably, in the above-mentioned method for treating organic wastewater, the oxidant is at least one of potassium periodate, sodium persulfate, hydrogen peroxide and sodium sulfite, preferably potassium periodate.
[0019] Further preferably, in the above-mentioned method for treating organic wastewater, the organic pollutant is at least one of golden orange II, neutral red, Congo red, methyl violet and the like.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] (1) The present invention uses a two-step method of double chloride corrosion-heat treatment to prepare an Fe-based bifunctional monolithic catalyst. - The ions have strong penetration and depassivation properties, converting metal foam iron into bimetallic (metal Fe and metal M) hydroxides, and then converting the bimetallic hydroxides into bimetallic oxides through heat treatment. The biggest advantage of this process is that the active material can be grown in situ on the substrate surface, thereby effectively avoiding the shedding of the active material and significantly improving the stability of the catalyst. At the same time, using low-cost transition metals as raw materials, the foamed iron not only serves as a supporting material, but also provides an Fe source for the catalyst, thereby avoiding the addition of additional Fe sources and reducing production costs.
[0022] (2) The present invention cleverly utilizes the harmful phenomenon of iron corrosion to prepare highly efficient catalytic materials, thus achieving the purpose of "turning waste into treasure". The preparation method is innovative and simple to operate. The prepared Fe-based bifunctional monolithic catalyst can utilize highly active sites to activate the activator potassium periodate, and the catalytic degradation method based on the non-radical reaction that generates electron transfer can achieve efficient removal of pollutants in organic wastewater.
[0023] (3) The preparation process of the Fe-based bifunctional integral catalyst of the present invention is simple, energy-saving, and time-saving, and can significantly reduce the preparation cost, and is particularly suitable for the field of sewage treatment. In addition, compared with traditional powder catalysts, the present invention avoids the problems of difficult recovery, low catalyst utilization, and more precipitation during the reaction, and improves the overall efficiency and economy of the catalyst. Moreover, the catalyst is non-toxic and harmless, environmentally friendly, and has important ecological and environmental significance, especially in the field of water treatment in my country. It has a wide range of application prospects and plays a positive role in promoting the progress of ecological and environmental protection technology.
[0024] (4) The bimetallic catalyst supported by the foamed iron prepared by the present invention can quickly activate periodate to generate active free radicals and efficiently degrade organic pollutants. The bimetallic catalyst supported by the foamed iron has a stable three-dimensional macroporous structure and abundant interface sites. At the same time, there is efficient mass transfer, enhanced electron transfer capacity and strong synergistic effect between the metallic iron and the metal M in the material. This unique morphology and synergistic effect ensure that it has excellent activity and durability in degrading various organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the material C precursor obtained in step 2 in Example 1;
[0026] Figure 2 This is a SEM image of the MnFe-IF-300 catalyst prepared in Example 1;
[0027] Figure 3 TEM of the MnFe-IF-300 catalyst prepared in Example 1 ( Figure 3 (a)) and HRTEM( Figure 3 (b) in the above);
[0028] Figure 4 Element Mapping diagram of the MnFe-IF-300 catalyst prepared in Example 1;
[0029] Figure 5 (a) is the XRD pattern of MnFe-IF catalyst samples obtained at different calcination temperatures, and (b) is the XRD pattern of MFe-IF catalyst samples obtained by corrosion of foamed iron by different metals;
[0030] Figure 6The degradation diagram of different organic pollutants by the MnFe-IF-300 catalyst prepared in Example 1;
[0031] Figure 7 This is a graph showing the degradation of golden orange II by the MnFe-IF-300 catalyst prepared in Example 1 under different oxidants;
[0032] Figure 8 The degradation diagram of golden orange II by Fe-based bifunctional monolithic catalysts prepared at different calcination temperatures;
[0033] Fig. 9 The degradation diagram of golden orange II by Fe-based bifunctional monolithic catalysts prepared with different metals;
[0034] Fig.10 This is a repeatability experimental diagram of the degradation of golden orange II by the MnFe-IF-300 catalyst prepared in Example 1;
[0035] Fig.11 The XPS spectra of the MnFe-IF-300 catalyst before and after the first reaction and the Fe-IF catalyst as a comparison;
[0036] Fig.12 This is a graph showing the degradation of Golden Orange II by the MnFe-IF-300 catalyst prepared in Example 1 under different pH conditions;
[0037] Fig.13 This is a graph showing the degradation of golden orange II by the MnFe-IF-300 catalyst prepared in Example 1 in the presence of different anions;
[0038] Fig.14 This is the degradation diagram of Golden Orange II by the MnFe-IF-300 catalyst prepared in Example 1 under different water qualities. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments, and the preferred embodiments herein are only used to illustrate and explain the present invention.
[0040] 1. Preparation of Fe-based bifunctional monolithic catalyst
[0041] Example 1
[0042] In this example, the Fe-based bifunctional monolithic catalyst was prepared according to the following steps:
[0043] Step 1: Make the size 2*2cm 2The foamed iron was immersed in 0.1 mol / L dilute hydrochloric acid and ultrasonically cleaned for 15 min to remove oxides on the surface of the foamed iron, then rinsed with ultrapure water to remove residual dilute hydrochloric acid, and then immersed in anhydrous ethanol and ultrasonically cleaned for 15 min to remove organic pollutants on the surface of the foamed iron. After the ultrasonic treatment, it was rinsed with anhydrous ethanol and finally dried in a vacuum oven at 60°C for 6 h to obtain material A.
[0044] Step 2: Dissolve the dichloride NaCl and MnCl2·4H2O in 100 mL of ultrapure water and stir evenly to obtain material B, wherein the concentrations of NaCl and MnCl are both 0.5 mol / L. Add material A into material B and stir at room temperature for 14 hours to obtain material C through a spontaneous metal corrosion process.
[0045] Step 3: Wash material C with ultrapure water and anhydrous ethanol in turn, and then place the washed material C in a vacuum oven at 60°C for 6 hours to obtain material D. Place material D in a quartz boat, and then place the quartz boat in a tube furnace and calcine at 300°C for 60 minutes (nitrogen protection, heating rate of 2°C / minute). After cooling to room temperature, an Fe-based bifunctional monolithic catalyst can be obtained, which is recorded as MnFe-IF-300.
[0046] Example 2
[0047] In this example, an Fe-based bifunctional integral catalyst was prepared in the same manner as in Example 1, with the only difference being that the calcination temperature in step 3 was adjusted to 200°C or 400°C. The obtained samples were recorded as MnFe-IF-200 and MnFe-IF-400, respectively.
[0048] Example 3
[0049] In this example, an Fe-based bifunctional integral catalyst was prepared by the same method as in Example 1, with the only difference being that MnCl2·4H2O was replaced with ZnCl2, CoCl2·6H2O, and NiCl2·6H2O of equimolar concentrations. The obtained samples were recorded as ZnFe-IF-300, CoFe-IF-300, and NiFe-IF-300, respectively.
[0050] Comparative Example 1
[0051] In this example, the Fe-based bifunctional integral catalyst was prepared in the same manner as in Example 1, except that the amount of MnCl2·4H2O added in step 2 was 0.
[0052] 2. Characterization of Fe-based bifunctional monolithic catalysts
[0053] 1. Characterization
[0054] Figure 1This is a SEM image of the material C precursor obtained in step 2 in Example 1. It can be seen from the image that the foamed iron after double salt etching is uniformly covered with nanoparticles and has a fluffy and porous structure. Figure 2 This is a SEM image of the MnFe-IF-300 catalyst prepared in Example 1. It can be seen from the image that after high-temperature calcination, the metal particles on the foam iron substrate become finer and denser. Figure 3 TEM of the MnFe-IF-300 catalyst prepared in Example 1 ( Figure 3 (a)) and HRTEM( Figure 3 (b) in the figure shows that the surface of the sample is loaded with Fe2O3 nanoparticles after high-temperature calcination. Figure 4 This is the element mapping diagram of the MnFe-IF-300 catalyst prepared in Example 1. It can be seen from the figure that Mn, Fe, and O are evenly distributed on the foamed iron. Figure 5 (a) in the figure is the XRD pattern of the MnFe-IF catalyst samples obtained at different calcination temperatures. It can be seen from the figure that the calcined Fe-based bifunctional monolithic catalyst has a strong peak at 44.67° and 65.1°, which is a typical characteristic peak of iron produced by the iron foam substrate. The Fe2O3 (311) plane has a peak at 43.4°, which is caused by oxidation of the foam iron during the calcination process. It is worth noting that no manganese was detected in the Fe-based bifunctional monolithic catalyst, which may be due to the high dispersion of MnOx on the catalyst. Figure 5 (b) is the XRD pattern of the MFe-IF catalyst samples obtained by corrosion of foamed iron by different metals, all of which show strong synthetic iron peaks.
[0055] 2. Characterization of degradation performance of organic pollutants
[0056] (1) Prepare a 20 mg / L solution of golden orange II (or neutral red, Congo red, methyl violet) to simulate organic pollutants (V = 200 mL), add 0.1 g / L potassium periodate PI (or sodium persulfate PDS, hydrogen peroxide and sodium sulfite) and a piece of MnFe-IF-300 catalyst prepared in Example 1, react at 25 ° C for 25 min, take samples at different times of the reaction, measure the concentration of pollutants using an ultraviolet spectrophotometer and calculate the removal rate of toxic organic pollutants.
[0057] Figure 6 This is the degradation diagram of MnFe-IF-300 catalyst for different organic pollutants. When PI is used as the oxidant, the degradation rates of golden orange II, neutral red, Congo red, and methyl violet are 96.2%, 85.4%, 86.9%, and 89.8%, respectively. This proves that the Fe-based bifunctional integral catalyst has a good removal rate for different organic pollutants. Figure 7This is the degradation diagram of Golden Orange II by MnFe-IF-300 catalyst under different oxidants. The degradation performance of Golden Orange II in PDS, Na2SO3 and H2O2 systems are 89.5%, 50.1% and 40.4%, respectively. Figure 8 The degradation diagram of golden orange II by MnFe-IF monolithic catalyst prepared at different calcination temperatures is shown in Figure 2. Fig. 9 This is the degradation diagram of golden orange II using Fe-based bifunctional monolithic catalysts prepared with different metals.
[0058] (2) Stability test of Fe-based bifunctional monolithic catalyst
[0059] A 20 mg / L solution of Golden Orange II was prepared to simulate organic pollutants (V=200 mL), and 0.1 g / L potassium periodate and a piece of MnFe-IF-300 catalyst prepared in Example 1 were added at the same time, and the reaction was carried out at 25°C for 25 min. Samples were taken at different reaction times, and the concentration of pollutants was measured using an ultraviolet spectrophotometer and the removal rate of toxic organic pollutants was calculated. After completing one test, the MnFe-IF-300 catalyst was taken out, rinsed with deionized water and anhydrous ethanol, and dried, and then the degradation experiment was carried out again in the same way to test its repeatability.
[0060] Fig.10 This is a repeatability test diagram of the degradation of golden orange II by MnFe-IF-300 catalyst. It can be seen from the figure that the prepared material still shows a good degradation effect after 4 repetitions, which can prove that the Fe-based bifunctional monolithic catalyst has stable catalytic activity in the Fe-based bifunctional monolithic catalyst / potassium periodate system. This shows that the Fe-based bifunctional monolithic catalyst has good reusability in the degradation process of golden orange II. Fig.11 The XPS spectra of MnFe-IF-300 and Fe-IF-300 before and after the first reaction are shown in Figure 2. The XPS survey spectra show the presence of Mn, Fe and O elements, and the peaks at 528-533, 640-655 and 708-727 eV belong to O1s, Mn 2p and Fe 2p, respectively.
[0061] (3) Effect of different pH environments on catalyst performance
[0062] A 20 mg / L golden orange II solution was prepared to simulate organic pollutants (V=200 mL), the pH of the pollutants was 3.01-7.96, and 0.1 g / L potassium periodate PI and a piece of MnFe-IF-300 catalyst prepared in Example 1 were added at the same time. The reaction was carried out at 25°C for 25 min, and samples were taken at different times of the reaction. The concentration of the pollutants was measured using an ultraviolet spectrophotometer and the removal rate of the toxic organic pollutants was calculated.
[0063] Fig.12This is the degradation diagram of Golden Orange II by MnFe-IF-300 catalyst under different pH conditions. It can be seen from the figure that the Fe-based bifunctional integral catalyst can exhibit good catalytic performance in a wide pH range.
[0064] (4) Effects of different anions on catalyst performance
[0065] Prepare 20 mg / L Golden Orange II solution to simulate organic pollutants (V = 200 mL), add 0.5 mM Cl - 、NO3 - 、SO4 2- 、HCO3 - , 0.1 g / L potassium periodate PI and a piece of MnFe-IF-300 catalyst prepared in Example 1 were added at the same time, and the reaction was carried out at 25° C. for 25 min. Samples were taken at different times of the reaction, and the concentration of pollutants was measured using an ultraviolet spectrophotometer and the removal rate of toxic organic pollutants was calculated.
[0066] Fig.13 This is the degradation diagram of Golden Orange II by MnFe-IF-300 catalyst in the presence of different anions. From the figure, it can be seen that the catalytic performance of the Fe-based bifunctional integral catalyst is not greatly disturbed under the interference of different anions, and it still has a good degradation effect on Golden Orange II.
[0067] (5) Effect of different water qualities on catalyst performance
[0068] Deionized water, pond water and river water were used to prepare 20 mg / L golden orange II solution to simulate organic pollutants (V=200 mL), and 0.1 g / L potassium periodate PI and a piece of MnFe-IF-300 catalyst prepared in Example 1 were added. The reaction was carried out at 25°C for 25 min. Samples were taken at different reaction times, and the concentration of pollutants was measured using an ultraviolet spectrophotometer, and the removal rate of toxic organic pollutants was calculated.
[0069] Fig.14 This is the degradation diagram of Golden Orange II by MnFe-IF-300 catalyst under different water qualities. It can be seen from the figure that the Fe-based bifunctional integral catalyst has a good degradation effect on Golden Orange II in different actual water bodies. This proves that the Fe-based bifunctional integral catalyst has strong anti-interference performance when exerting its catalytic effect and is of great practical application value.
[0070] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an Fe-based bifunctional monolithic catalyst based on a double chloride water corrosion method, characterized in that: Proceed as follows: Step 1, washing the foamed iron with dilute hydrochloric acid, ultrapure water and anhydrous ethanol in sequence, and finally drying it in an oven to obtain material A; Step 2, dissolving dichloride NaCl and MCl in ultrapure water, stirring evenly to obtain material B; placing material A into material B, stirring at room temperature, and obtaining material C through a spontaneous metal corrosion process; Step 3, washing material C with ultrapure water and anhydrous ethanol in turn, and then placing the washed material C in an oven to dry to obtain material D; finally, placing material D in a tubular furnace and calcining under the protection of an inert gas to obtain the target product.
2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the dilute hydrochloric acid is 0.1-1 mol / L.
3. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of NaCl and MCl constituting the double chloride is 0.5:0.1-0.5, wherein M is Mn, Ni, Zn or Co.
4. The preparation method according to claim 1, characterized in that: In step 2, the stirring time at room temperature is 12 to 16 hours.
5. The preparation method according to claim 1, characterized in that: In step 3, the calcination conditions are: firstly, heating to 200-500° C. at a heating rate of 2-3° C. / min, keeping the temperature for 1-2 hours, and then naturally cooling to room temperature.
6. The preparation method according to claim 1, characterized in that: In step 1 and step 3, the drying is carried out at 60-80° C. for 6-10 hours.
7. An Fe-based bifunctional integral catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the Fe-based bifunctional monolithic catalyst according to claim 7 in the treatment of organic wastewater, characterized in that: In the presence of the Fe-based bifunctional integral catalytic material, wastewater containing organic pollutants contacts and reacts with an oxidant, and purified water is obtained after the reaction.
9. The use according to claim 8, characterized in that: The oxidant is at least one of potassium periodate, sodium persulfate, hydrogen peroxide and sodium sulfite.
10. The use according to claim 8, characterized in that: The organic pollutant is at least one of golden orange II, neutral red, Congo red and methyl violet.
Citation Information
Patent Citations
Method for treating nitrogenous wastewater by using iron-carbon complexing agent
CN103951016A
Preparation method of carbon cloth load nickel oxide coated iron oxide nanorod composite material
CN106229153A
Ferronickel hydroxide electrocatalyst, preparation method and application thereof, self-powered system and application thereof
CN111313041A
Preparation method of super-hydrophobic foam iron surface and application of super-hydrophobic foam iron in oily wastewater treatment
CN112981400A
Universal method for preparing self-supporting layered metal hydroxide
CN114134531A